Faktor Penentu Profitabilitas Bank Tercatat di Indonesia: Pendekatan dengan Regresi Kuantil - Restiana Ie Tjoe Linggadjaya; Apriani Dorkas Rambu Atahau; Gracia Shinta S. Ugut; Kim Sung Suk (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2024)
This quantitative study examines 6 predictors that are presumed to affect profitability for listed banks in Indonesia. The purpose of this study is to examine the determinants of profitability and the magnitude of the influence of such determinant on profitability of listed banks in Indonesia. This study uses the entire population of listed banks in Indonesia and focused on the period from 2013 to 2022 with a total of 47 listed banks. The statistical analysis instrument used is panel data quantile regression using R. Bank profitability is measured by return on assets (ROA), whereas liquidity, assets quality, asset management, leverage, efficiency, and capital adequacy are used as bank‐specific factors. The research result are that asset quality, asset management, capital adequacy affect bank profitability significantly and positively, while asset quality and efficiency negatively affect profitability. Meanwhile, LDR has a negative relationship with profitability. The novelty of this study is that it is the first study on the determinants of profitability for banks registered in Indonesia using quantile regression. The results of quantile regression provide deeper insight than OLS linear regression or fixed effect panel regression because it can describe the distinctive influence and direction of each quantile of profitability. Quantile regression analysis of profitability has been carried out on return on assets, and not yet being performed on net interest margin and return on equity. Suggestions for future research to add a lagged effect (t-1) for asset quality to profitability and also add robustness check.